Challenges for food subsidy reform: Lessons learnt from the Just Distribution of Subsidies Scheme in Iran - Ali Akbar Tajmazinani (German Institute of Development and Sustainability (IDOS), 2024)
While there is increasing consensus in the academic debate on the regressive nature of energy subsidies and the necessity to reduce them, this is much less so for food subsidy reforms - not least because of the positive impact of food subsidies for food security. They make food affordable even for lower-income households, and therefore they are often important for the well-being of this group. In addition, food subsidy reforms can be designed in different ways and have quite different effects. Badly designed programmes may cause more harm than good. Many countries in the world, including in the MENA region, struggle thus with the question of whether, and under which conditions, it is recommendable to reduce food subsidies. This discussion paper examines the most recent experience of food subsidy reform in Iran in order to derive some lessons for food subsidy reforms elsewhere. Iran has a long history of providing general commodity subsidies, including for energy and food items, and it has attempted several waves of subsidy reforms in the past three decades, most notably in 2010 (energy and bread) and 2019 (petrol), whereby it established a nationwide direct cash transfer system. However, given the political and economic circumstances, subsequent administrations have returned to different kinds of consumer subsidies, which have required further reforms. The most recent form of food subsidy was the preferential foreign exchange rate (PFER) policy, which allocated about US100 billion of the government's foreign exchange reserves with a fixed rate (far below the market rate) - during the four years following the unilateral withdrawal of United States from the Iran nuclear deal in 2018 - to import food and other basic commodities. Finally, the Raisi administration abolished the PFER policy in May 2022 and started to redistribute what it saved from the consumer subsidy cuts through the Just Distribution of Subsidies Scheme (JDSS), which is actually a targeted direct cash transfer scheme. The main question of this discussion paper is: Under which conditions is a reduction or full elimination of food subsidies recommendable, given the experiences of Iran with its most recent reform (the replacement of consumer subsidies by targeted direct cash transfers paid out by the JDSS), and what challenges might such a reform entail? A secondary analysis of national data on "household expenditures" and "price index" is used to calculate future changes in household living expenditures in the short and medium terms, and to determine winners and losers of the new policy. Moreover, a thematic analysis of published contents (interviews, columns, articles and public speeches) about the scheme from key experts - before and after the launch of the scheme - is used to map out various aspects of the successes and failures of the scheme. Our findings indicate that the way food subsidy reforms are designed and at what moment they are implemented matter a lot with regard to their effects. In the Iranian case, several factors could undermine the success of the recent food subsidy reform. First, ignoring the framework conditions of reform - including both international and domestic factors (such as economic instability, diminishing vertical trust, a lack of smooth foreign relations, budget deficit and low standards of good governance) - can jeopardise the reform or nullify its effects. Second, the lack of an "indexation element" (for the level of cash transfers) in an environment of continually increasing inflation and currency devaluation lead to a rapid decline in the purchasing power of cash transfers. Third, implementation shortcomings, such as targeting errors (due to weaknesses of the Iranians' Welfare Database), delivery deviations and a lack of transparency, lead to serious levels of mistrust. Ultimately, all of the above-mentioned challenges in the design and implementation of the scheme seem to hamper its objectives with regard to food security, poverty reduction, promotion of income equality and the abolition of corruption. As a consequence we recommend that policy-makers (i) bear in mind the effect of national and international framework conditions (such as uneven international relations, economic situation, high inflation, diminishing vertical trust and chronic budget deficits) on the possible success of the reform; (ii) consider prioritising other, more urgent economic reforms (such as reforming the budgeting, banking and taxation systems) instead of reforming food subsides, which may be vital for the food security of the lowest income groups of the population; (iii) set an "indexation element" in the scheme and raise the cash amount and/or provide a fixed package of food items in a timely manner; (iv) control for possible targeting errors in the compensation element of the food subsidy reform before launching the scheme and during its implementation; and (v) make sure that any scheme that is meant to compensate for the subsidy cuts, such as a direct cash transfer scheme, is well-embedded in the overall social protection system of the country.
Keywords: 320; Subsidy reform; food subsidy; cash transfer; redistribution; inflation; Iran